2019
DOI: 10.1002/pros.23900
|View full text |Cite
|
Sign up to set email alerts
|

Family history is significantly associated with prostate cancer and its early onset in Chinese population

Abstract: Background: Family history (FH) of prostate cancer (PCa) in Chinese population is poorly understood. The objective of this study is to evaluate the association between FH and PCa in a Chinese biopsy cohort.Methods: Consecutive patients who received 10 to 12 core systematic prostate biopsies from April 2013 to October 2018 in three medical centers were enrolled in this study.Demographic information and clinical information were obtained through prebiopsy questionnaire, including cancer FH, age, and total prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Similarly to already recognised and currently extensively discussed epidemic developments of other noncommunicable diseases such as type 2 diabetes [15] and breast cancer [16,17], the PCa management paradigm obviously requires a fundamental revision meeting needs of young populations [18], individuals at risk by both genetic and modifiable factors [19,20] as well as stratified patient cohorts benefiting from individualised treatment algorithms [21]. The article summarises knowledge accumulated in regard to the PCa-relevant non-modifiable and modifiable risk factors, highlights current deficits in PCa managements and presents innovative solutions in the context of predictive, preventive and personalised (3P) medicine (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to already recognised and currently extensively discussed epidemic developments of other noncommunicable diseases such as type 2 diabetes [15] and breast cancer [16,17], the PCa management paradigm obviously requires a fundamental revision meeting needs of young populations [18], individuals at risk by both genetic and modifiable factors [19,20] as well as stratified patient cohorts benefiting from individualised treatment algorithms [21]. The article summarises knowledge accumulated in regard to the PCa-relevant non-modifiable and modifiable risk factors, highlights current deficits in PCa managements and presents innovative solutions in the context of predictive, preventive and personalised (3P) medicine (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a positive FH of prostate cancer (PCa) or BRCA‐related cancers was related to an earlier age at onset of PCa. 21 Besides, FH of colorectal cancer (CRC) was also considered to be associated with early-onset CRC (age <50 years). 22 The unusual discovery in this study of RCC has not been reported in any other epidemiological research, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Reports revealed that the United States is expected to spend more than US$8 billion annually on the screening and treatment of PCA 2 . Incidence of PCA in China is lower than in the United States; however, in the past two decades, numbers of PCA patients have increased significantly due to environmental pollution, westernized change in diet, and aging of the population 3 . The prostate-specific antigen (PSA) is currently recognized as a useful tool for early screening of PCA 4 .…”
Section: Introductionmentioning
confidence: 93%
“…Compared to PPARG1, PPARG2 contains 30 additional amino acids at the N terminus and the ligand-independent activation activity is 5–10 times than that of PPARG1 12 . It has been reported that PPARG plays a role in a variety of chronic diseases including tumors 3 , 13 , diabetes 14 , inflammation 15 , atherosclerosis 16 , and so on. As far as PPARG2 is concerned, its role in PCA has not been clarified.…”
Section: Introductionmentioning
confidence: 99%